Tom sawyer - Brook, Henry; McNee, Ian Twain, Mark (Usborne London, 2014)
Tom Sawyer dreams of becoming a pirate, an explorer or an outlaw. But after witnessing a gruesome crime, he embarks on an adventure far more thrilling than he could have imagined. Mark Twain's classic story rivetingly retold for younger readers